Analisis Cerpen "Tangan-Tangan Buntung" Karya Budi Darma dengan Pendekatan Psikologis - Putri, Viola Syahdriati; Abdurrahman, Abdurrahman (TSAQOFAH, 2026)
Literary psychology offers a critical perspective for understanding the psychological complexity of characters in literary works, yet analyses that specifically examine the representation of trauma and inner conflict in Budi Darma’s short story Tangan-Tangan Buntung remain relatively limited. This study aimed to analyze the short story using a psychological approach, focusing on the main character’s mental condition, the dynamics of inner conflict, and the representation of traumatic experiences that shape the character’s behavior and worldview. A qualitative descriptive method was employed through textual analysis, examining narrative structure, symbols, dialogue, and character actions based on concepts of literary psychology. The analysis shows that the main character experiences psychological pressure in the form of anxiety, a persistent sense of threat, and perceptual distortions triggered by traumatic experiences and an unstable environment. These psychological symptoms structure the character’s patterns of interaction with his surroundings and create a narrative atmosphere that is dark, tense, and filled with uncertainty. The findings affirm that through powerful symbolization and characterization, Budi Darma successfully presents a complex representation of the human mental condition in extreme situations, thereby enriching our understanding of the application of literary psychology in the analysis of modern Indonesian short stories.